2022
DOI: 10.1037/trm0000314
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms and posttraumatic growth in a community sample exposed to stressful events: A (not so) curvilinear relationship.

Abstract: The relationship between posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG) has been extensively debated, with evidence supporting that negative and positive outcomes may coexist simultaneously. However, literature consensus has yet to be reached regarding whether the nature of the relationship between these variables is better explained through a linear or curvilinear relationship. In the present study, we examined the psychometric properties of the Posttraumatic Growth Inventory and tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The potential for psychological growth after trauma is less well studied than the more physiological consequences of trauma (70, 71) and may add an important perspective to current thinking about trauma. PTG can be transformative; in the face of emotionally overwhelming and stressful events, individuals can commit their resources and skills toward overcoming adversity and emerge with a perception of an improvement in themselves (72)(73)(74). This process in survivors of intensive care for COVID-19 has been studied little.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for psychological growth after trauma is less well studied than the more physiological consequences of trauma (70, 71) and may add an important perspective to current thinking about trauma. PTG can be transformative; in the face of emotionally overwhelming and stressful events, individuals can commit their resources and skills toward overcoming adversity and emerge with a perception of an improvement in themselves (72)(73)(74). This process in survivors of intensive care for COVID-19 has been studied little.…”
Section: Discussionmentioning
confidence: 99%
“…The PTS-PTG curvilinear model A and corresponding theories are so well-established that recent studies finding linear relationships have still couched these findings within the engine framework, concluding that homogenous trauma severity within the study is the reason only linear effects were found (Maia et al, 2022;Thomas et al, 2021). Therefore, a next step for understanding PTG in the context of PTS is to examine the PTS-PTG relationship while accounting for trauma severity.…”
Section: Curvilinear Relationships Between Ptg and Symptomsmentioning
confidence: 99%
“…The current literature suggests a complex association between PTG and PTS. Some studies on PTS and PTG report that the relationship is inconsistent, for they appear positively correlated at times (Cleary et al, 2022; Maia et al, 2022), inversely correlated at times (Stermac et al, 2014; Thomas et al, 2021), and uncorrelated at times (Salsman et al, 2009; Taku et al, 2021). Although some scholars continue to debate the direction of this relationship, an abundance of literature suggests that the relationship between PTG and PTS is most likely curvilinear (Dar & Iqbal, 2020; Elderton et al, 2017; Greenberg et al, 2021; Shakespeare-Finch & Lurie-Beck, 2014).…”
Section: Curvilinear Relationships Between Ptg and Symptomsmentioning
confidence: 99%
“…Accordingly, PTG is associated with measures of positive well-being and flourishing (Grier-Reed et al, 2023; Helgeson et al, 2006). As such, one’s perceptions of positive changes emerging after a trauma experience may indicate an important aspect of adaptation but may also coexist alongside PTSS (Maia et al, 2022).…”
mentioning
confidence: 99%